Organoclay as a Highly Efficient Catalyst for Three-Component One-Pot Biginelli Synthesis of Octahydroquinazolinone Derivatives - Sayyahi, Soheil (Asian Journal of Chemistry, 2013)
In this study, the synthesis of octahydroquinazolinone derivatives via three-component Biginelli reaction is reported. The organoclay-catalyzed process proved to be simple, efficient and environmentally friendly.